ON DECODING ALGORITHMS FOR GENERALIZED REED — SOLOMON CODES WITH ERRORS AND ERASURES. II - Ratseev, S. M.; Cherevatenko, O. I. (Vestnik of Samara University Natural Science Series, 2022)
The article is a continuation of the authors work On decoding algorithms for generalized Reed Solomon codes with errors and erasures. In this work, another modification of the Gao algorithm and the Berlekamp Massey algorithm is given. The first of these algorithms is a syndrome-free decoding algorithm, the second is a syndrome decoding algorithm. The relevance of these algorithms is that they are applicable for decoding Goppa codes, which are the basis of some promising post-quantum cryptosystems.